TINGKAT PEMENUHAN AKTIVITAS SEHARI – HARI PASIEN SKIZOFRENIA DI LINGKUP KERJA PUSKESMAS GOMBONG II - Lilis Tri Hardani; Basirun -; sawiji - (Jurnal Ilmiah Kesehatan Keperawatan, 2009)
Schizophrenia is one of the mental illness. It’s psychoses functional disorders. One its characteristics is decreasing daily activities. Schizophrenia patients are commonly still helped by their family in doing daily activities in the society. The objective of the research was to find out daily activities accomplishment level of schizophrenics patients in community health center II Gombong. Populations were taken by using purposive sampling to the family who had schizophrenic patient in community health center II Gombong. There were 32 respondents as the samples.  The research used cross sectional approach where the researcher only described daily activities accomplishment level of schizophrenics patients in community health center II Gombong. The data were collected by using check list questionnaire consisted of 25 questions: 6 questions about personal hygiene activities, 8 questions about dressing and make upping activities, 6 questions about having meal activities, and 5 questions about urinate and defecation activities. The result finding showed that, 38% of schizophrenics patients were in the category of light dependent, 28% in the category of medium dependent, 13 % were in the category of hard dependent, 13% were in the category of total dependent, and 3% were in the category of independent. Daily activities accomplishment level of schizophrenics patients in community health center II Gombong The highest percentage were in the category of light dependent.   Keywords; schizophrenics patients, daily activities.